PENGGUNAAN MODEL PEMBELAJARAN IQRA DALAM MENGEMBANGKAN KARAKTER RELIGIUS DAN PEDULI LINGKUNGAN - Deni Nasir Ahmad; Luluk Setyowati (JURNAL HURRIAH: Jurnal Evaluasi Pendidikan dan Penelitian, 2021)
The purpose of this study was to find out the use of the Iqra' learning model in developing religious and environmental character. Literature review method where researchers take several research articles that have been published in national journals and national proceedings. The results of the research, namely from the two characters, namely religious characters and caring for the environment, provide an explanation that the Iqra learning model is very suitable to be used in character cultivation because it emphasizes learning experiences and solutions in solving problems that exist in the environment. It can be concluded that learning with the Iqra 'model is very suitable for inculcating characters, namely religious characters and caring for the environment because learning activities are in the form of inviting students to participate in all learning activities.